Tapioca quality observation based on physical and chemical properties of products - Rahmadhia, Safinta Nurindra; Wuryantoro, Wuryantoro; Ayuningtyas, Diah (Universitas Ahmad Dahlan, 2022)
PT Sinar Pematang Mulia, located in the Mataram Udik area, Central Lampung, is a company engaged in the tapioca flour industry with a production capacity of 500 tons/day. The purpose of the observation in this practical work is to determine whether the tapioca flour product of PT Sinar Pematang Mulia II is following the SNI for the quality of tapioca flour. The methods used include data collection and interviews. The analysis carried out as a determinant of the quality of the finished goods product is the analysis of water content, pH, retain a sample of 100 mesh, impurities mesh 325, SO2, ash content, starch content, whiteness, acid degree, and viscosity. Data were collected by analyzing for seven days and comparing the value of the analysis results with the standard of SNI tapioca flour and PerKBPOM no. 36 of 2013. It can be seen that in all the results of the analysis carried out, none of them exceeds the maximum limit.